Constraints Experienced by Homestead Vegetable Growers in Kollam District - Chandran, Vani; Podikunju, Bindu (Indian Journal of Extension Education, 2021)
Homestead or home gardens represent a promising land use system and are common in Kerala, where the average size of farm households is small. The present investigation was carried out in the homesteads of selected panchayaths of Kollam district during 2017-18 with an objective to measure the constraints perceived by the homestead vegetable growers in vegetable cultivation. Twenty homesteads were selected randomly from each identified panchayat, thus making the total sample size 120 homesteads. To measure the constraints faced by the respondents in vegetable production, a suitable schedule was developed and the constraints were ranked accordingly based on the total score obtained by summing up the total score for each constraint. Based on the obtained score, scarcity of water resources, prevalence of pest and diseases, price fluctuation, high labour charges, high cost of cultivation, labour scarcity, non availability of inputs in time, non assurance of premium price for organic products, were the major constraints reported by the homestead vegetable growers.
Keywords: Constraints; Crop management constraints; Economic constraints; Homestead vegetable growers; Suggestions